2021
DOI: 10.1039/d1ee00918d
|View full text |Cite
|
Sign up to set email alerts
|

Constructing an n/n+ homojunction in a monolithic perovskite film for boosting charge collection in inverted perovskite photovoltaics

Abstract: The suboptimal carrier dynamics at perovskite/electron transport layer has largely limited the further performance enhancement of the state-of-the-art inverted p-i-n structured perovskite solar cells. Herein, we discovered that a simple...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 49 publications
1
72
0
Order By: Relevance
“…This would enable a suitable band bending and better energy‐level alignment, which are beneficial for charge transfer and the V oc improvement. [ 21,45 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would enable a suitable band bending and better energy‐level alignment, which are beneficial for charge transfer and the V oc improvement. [ 21,45 ]…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the gas‐quenching method has great potential for cost‐effective and large‐area device manufacturing, but the performance of gas‐quenched devices is currently lower than that of the state‐of‐the‐art devices fabricated with antisolvent‐assisted deposition. [ 20–23 ] So far, with various film and device optimization strategies, highly efficient gas‐quenched n–i–p PSCs with a best PCE of 23.6% have been reported. [ 24–27 ] As for the gas‐quenched inverted p–i–n PSCs, Liu et al obtained PCEs of 22.07% using a multifunctional sulfobetaine‐based zwitterionic surfactant to improve the film quality.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the devices exhibited an outstanding V oc and FF values of 1.17 V and 83%, respectively, with the best device reaching a PCE of 21.4%. Lu et al [ 137 ] demonstrated that a simple modification of the perovskite surface with a trace amount of indium bromide (InBr 3 ) enabled beneficial n‐doping of the perovskite films, which effectively enhanced charge collection at the perovskite/C 60 interface. They concluded that the facilitated charge separation can be attributed to a n/n + homojunction between the bulk (weak n type (n) component) and the surface (more n type (n + ) component) in the perovskite film.…”
Section: Interface Passivation Of Perovskitementioning
confidence: 99%
“…[ 9–13 ] With high feasibility and efficiency in managing directional migration of charge carriers, the internal electric field (IEF), are recently emerging as an up‐to‐date frontier in well modulating the bulk and surface charge dynamics for single‐component materials and interfacial charge dynamics for heterojunction systems, opening up a highway for advanced material design to high performance. [ 14,15 ]…”
Section: Introductionmentioning
confidence: 99%